A Study of Generalized Quasi-Hyperideals in Ordered Ternary Semihypergroups: Mohammad Y. Abbasi, Kostaq Hila, Sabahat A. Khan, Aakif F. Talee - Team, Support (Thai Journal of Mathematics, 2021)
In this paper, we introduce and study generalized quasi-hyperideals in ordered ternary semihypergroups. Also, we define some generalized kinds of hyperideals in ordered ternary semihypergroups and study the relation between them.